Gold‐Mediated Exfoliation of Ultralarge Optoelectronically‐Perfect Monolayers. Issue 21 (23rd March 2016) - Desai, Sujay B.; Madhvapathy, Surabhi R.; Amani, Matin; Kiriya, Daisuke; Hettick, Mark; Tosun, Mahmut; Zhou, Yuzhi; Dubey, Madan; Ager, Joel W.; Chrzan, Daryl; Javey, Ali
Abstract : Gold‐mediated exfoliation of ultralarge optoelectronically perfect monolayers with lateral dimensions up to ≈500 μm is reported. Electrical, optical, and X‐ray photoelectron spectroscopy characterization show that the quality of the gold‐exfoliated flakes is similar to that of tape‐exfoliated flakes. Large‐area flakes allow manufacturing of large‐area monolayer transition metal dichalcogenide electronics.